2002
DOI: 10.4269/ajtmh.2002.66.372
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte proliferation and antibody responses to Plasmodium falciparum liver-stage antigen-1 in a highland area of Kenya with seasonal variation in malaria transmission.

Abstract: Abstract. Lymphocyte proliferation and antibody responses to five peptides corresponding to the N-and C-terminal non-repeat and central repeat regions of Plasmodium falciparum liver-stage antigen-1 (LSA-1) were examined in residents of a highland area of Kenya where malaria transmission is episodic and varies with rainfall. The frequency of lymphocyte proliferation responses (stimulation index > 2) by children (persons Յ 6 years old) and adults (persons Ն 18 years old) was similar and did not differ significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
(27 reference statements)
5
17
1
Order By: Relevance
“…In the rainy season, the frequencies and levels of IgG antibodies to CSP and TRAP were similar in children and adults, but, as described previously, the frequencies and levels of IgG antibodies to LSA-1 were significantly lower in children than in adults (8). In the dry season, the frequencies and levels of antibodies to all three antigens were lower in children than in adults.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In the rainy season, the frequencies and levels of IgG antibodies to CSP and TRAP were similar in children and adults, but, as described previously, the frequencies and levels of IgG antibodies to LSA-1 were significantly lower in children than in adults (8). In the dry season, the frequencies and levels of antibodies to all three antigens were lower in children than in adults.…”
Section: Discussionsupporting
confidence: 81%
“…It was reported previously that the proportion of people with IgG, IgG1, and IgG3 subclass antibodies to LSA-1 decreased during a period of low transmission in a highland area of Kenya. However, antibodies to LSA-1 did not correlate with time to reinfection (8). In this paper, we describe IgG antibodies to the additional preerythrocytic antigens CSP and TRAP in these children and adults during the dry and rainy seasons and compare the frequencies and levels of these antibodies with those previously described for LSA-1 (8).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Malaria infection surveys conducted in Kabobo during periods of no or little rainfall have shown that the prevalence of blood-stage P. falciparum in symptom-free 5-to 10-year-old school children is 8.9%. The prevalence increased to 45.5% during a period of heavy rainfall (37,38).…”
Section: Study Design and Subjectsmentioning
confidence: 99%